"But no one told me it's okay to not drink": a qualitative study of young people who drink little or no alcohol. (March 2014) - Herring, Rachel; Bayley, Mariana; Hurcombe, Rachel
<x xml:space="preserve">Abstract</x> Young people's drinking is a matter of social, media, and political concern and the focus of much policy activity within the United Kingdom. Little consideration has been given to the fact that some young people choose to drink little or not all and our knowledge and understanding of their choices and how they manage not drinking is limited. Nor has much attention been paid to the possibility that the insights of young light and non-drinkers could be useful when thinking about how to change the prevailing drinking culture, but if we are to gauge and engage with the current culture of consumption then we need to understand all parts of it. This qualitative study of young people (aged 16–25) who drink little or no alcohol aimed to further understanding of their lives and choices. The results highlight that choosing not to drink or drink lightly is a positive choice made for diverse reasons with the strongest messages and influences coming from real-life observations. Young people develop strategies to manage not drinking or drinking lightly. Alcohol education messages need to present not drinking as a valid option to young people, parents, and society more broadly.